Alkylated benzimidazoles: Design, synthesis, docking, DFT analysis, ADMET property, molecular dynamics and activity against HIV and YFV. (December 2020) - Srivastava, Ritika; Gupta, Sunil K.; Naaz, Farha; Sen Gupta, Parth Sarthi; Yadav, Madhu; Singh, Vishal Kumar; Singh, Anuradha; Rana, Malay Kumar; Gupta, Satish Kumar; Schols, Dominique; Singh, Ramendra K.
Graphical abstract: Highlights: New benzimidazole analogs synthesized as antivirals against HIV-1 and yellow fever virus. Molecular dynamics simulation studies indicated a stable ligand-protein complex of compound 3a within NNIBP of HIV-RT. DFT analysis confirmed the stability of hydrogen bonding interaction between the TRP 229 residue of HIV-RT and compound 3a . Molecules were tested for their anti-HIV and broad spectrum antiviral properties against different DNA and RNA viruses. Antiviral properties and cytotoxicity determined using MTT assay. Compound 3a showed anti-HIV activity and compound 2b showed excellent inhibition property against yellow fever virus. Abstract: A series of alkylated benzimidazole derivatives was synthesized and screened for their anti-HIV, anti-YFV, and broad-spectrum antiviral properties. The physicochemical parameters and drug-like properties of the compounds were assessed first, and then docking studies and MD simulations on HIV-RT allosteric sites were conducted to find the possible mode of their action. DFT analysis was also performed to confirm the nature of the hydrogen bonding interaction of active compounds. The in silico studies indicated that the molecules behaved like possible NNRTIs. The nature – polar or non-polar and position of the substituent present at fifth, sixth, and N -1 positions of the benzimidazole moiety played an important role in determining the antiviral properties of the compounds. Among the various compounds, 2-(5, 6-dibromo-2-chloro-1 H -benzimidazol-1-yl)ethan-1-ol (3a ) showed anti-HIV activity with an appreciably low IC50 value as 0.386 × 10 −5 μM. Similarly, compound 2b, 3-(2-chloro-5-nitro-1 H -benzimidazol-1-yl) propan-1-ol, showed excellent inhibitory property against the yellow fever virus (YFV) with EC50 value as 0.7824 × 10 −2 μM.